Exploring the use of probiotics in dermatology – a literature review - Sroczyńska, Monika; Luchowska, Anna; Żaczek, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction Probiotics are defined as "live microorganisms which when administered in adequate amounts confer a health benefit on the host" by the World Health Organization (WHO). Probiotics help to regulate innate and adaptive host immune responses by combating aggressive commensal bacteria and improving epithelial barrier function. Probiotics have shown positive results in the treatment of various inflammatory skin conditions. Aim of the study The aim of the study was to investigate the potential efficacy of probiotics in the treatment of dermatological diseases, such as acne vulgaris; atopic dermatitis; psoriasis. Materials and methods A search was conducted using PubMed and Google Scholar databases. Articles were searched in English using the following key words: probiotics; dermatology; acne vulgaris; eczema; atopic dermatitis; psoriasis. Results Probiotics reduced the amount of inflammatory acne lesions and the erythema index in acne vulgaris patients. Patients with atopic dermatitis who received probiotics also experienced an immediate and long-lasting improvement in their symptoms and skin quality. Individuals noticed enhanced skin smoothness and moisture, self-acceptance, and a decrease in the SCORAD index. It was also proven that oral probiotic supplementation successfully reduced psoriasis symptoms by lowering plasma levels of inflammatory markers such as IL-6, TNF-α, and CRP. Furthermore, the chance of psoriasis recurrence was reduced. Conclusion The reviewed literature indicates that probiotics may be helpful in treating skin conditions like psoriasis, atopic dermatitis, and acne vulgaris. Probiotics demonstrated encouraging results in the treatment of inflammatory skin conditions by altering the immune response as a result of modifying the gut microbiome.